2014
DOI: 10.1111/sdi.12200
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Evidence on Hemodiafiltration: A Systematic Review and a Meta‐analysis

Abstract: The general objective assigned to the European DIALysis (EUDIAL) Working Group by the European Renal Association – European Dialysis and Transplant Association (ERA-EDTA) was to enhance the quality of dialysis therapies in Europe in the broadest possible sense. Given the increasing interest in convective therapies, the Working Group has started by focusing on hemodiafiltration (HDF) therapies. A EUDIAL consensus conference was held in Paris on 13 October 2011 to discuss definitions, safety standards, clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
110
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(117 citation statements)
references
References 24 publications
3
110
0
4
Order By: Relevance
“…The Turkish HDF and CONTRAST studies found no difference in mortality or cardiovascular events [15,16] whereas the ESHOL study reported a large (30%) reduction in all-cause mortality [17]. This evidence base is further complicated by the divergent results of four meta-analyses, all of which showed reductions in IDH with HDF but only one suggested improved patient outcomes [11][12][13][14]. A more recent pooled individual participant data analysis suggested a survival benefit with HDF, particularly with higher convection volumes [18].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The Turkish HDF and CONTRAST studies found no difference in mortality or cardiovascular events [15,16] whereas the ESHOL study reported a large (30%) reduction in all-cause mortality [17]. This evidence base is further complicated by the divergent results of four meta-analyses, all of which showed reductions in IDH with HDF but only one suggested improved patient outcomes [11][12][13][14]. A more recent pooled individual participant data analysis suggested a survival benefit with HDF, particularly with higher convection volumes [18].…”
Section: Discussionmentioning
confidence: 75%
“…To date, these findings have largely been generated using echocardiography to assess regional myocardial contractility [7,8], alongside two small studies using positron emission tomography (PET) to measure myocardial perfusion during HD [9,10]. On-line haemodiafiltration (HDF) is a modified haemodialysis (HD) modality incorporating increased convective clearance, which has long been reported to reduce intradialytic hypotension (IDH) [11][12][13][14]. However, despite three randomised controlled trials and several meta-analyses, opinion remains conflicted as to whether HDF improves patient outcomes and the mechanisms by which HDF may do so are not well elucidated [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Mostovaya et al [69] compared exclusively HDF to HD (low-and high-flux) including 2402 patients. The meta-analysis identified six RCTs.…”
Section: Meta-analysesmentioning
confidence: 99%
“…On the other hand, some studies suggested that high-flux filters cannot be practically used at all dialysis sessions for all patients because these filters are not often economically affordable. The patients cannot also tolerate these filters for long periods (14). Munshi et al showed that high-flux dialysis increases the risk of hemodynamic instability and disequilibrium syndrome although high-flux filters accelerate urea clearance more than low-flux filters at a zero ultrafiltration rate and blood flow and low dialysate flow rate (15).…”
Section: Introductionmentioning
confidence: 99%